Water stress and nitrogen supply affect floral traits and pollination of the white mustard, Sinapis alba (Brassicaceae) - Akter, Asma; Klečka, Jan (PeerJ, 2022)
Changes in environmental conditions are likely to have a complex effect on the growth of plants, their phenology, plant-pollinator interactions, and reproductive success. The current world is facing an ongoing climate change along with other human-induced environmental changes. Most research has focused on the impact of increasing temperature as a major driving force for climate change, but other factors may have important impacts on plant traits and pollination too and these effects may vary from season to season. In addition, it is likely that the effects of multiple environmental factors, such as increasing temperature, water availability, and nitrogen enrichment are not independent. Therefore, we tested the impact of two key factors-water, and nitrogen supply-on plant traits, pollination, and seed production in Sinapis alba (Brassicaceae) in three seasons defined as three temperature conditions with two levels of water and nitrogen supply in a factorial design. We collected data on multiple vegetative and floral traits and assessed the response of pollinators in the field. Additionally, we evaluated the effect of growing conditions on seed set in plants exposed to pollinators and in hand-pollinated plants. Our results show that water stress impaired vegetative growth, decreased flower production, and reduced visitation by pollinators and seed set, while high amount of nitrogen increased nectar production under low water availability in plants grown in the spring. Temperature modulated the effect of water and nitrogen availability on vegetative and floral traits and strongly affected flowering phenology and flower production. We demonstrated that changes in water and nitrogen availability alter plant vegetative and floral traits, which impacts flower visitation and consequently plant reproduction. We conclude that ongoing environmental changes such as increasing temperature, altered precipitation regimes and nitrogen enrichment may thus affect plant-pollinator interactions with negative consequences for the reproduction of wild plants and insect-pollinated crops.
Keywords: zemědělské plodiny; lidé; opylení; Pollination; Insect-pollinated crops; Sinapis alba; Crops, Agricultural; Water stress; dehydratace; Brassicaceae; Nitrogen enrichment; Dehydration; Temperature; Humans; Sinapis; hořčice rodu Sinapis